Proceedings of the first International Conference on Computational Intelligence and Informatics : ICCII 2016 - Satapathy, Suresh Chandra, 1964-; Prasad, V. Kamakshi; Rani, B. Padmaja; Udgata, Siba K.; Raju, K. Srujan (Springer, 2017)
The book covers a variety of topics which include data mining and data warehousing, high performance computing, parallel and distributed computing, computational intelligence, soft computing, big data, cloud computing, grid computing, cognitive computing, image processing, computer networks, wireless networks, social networks, wireless sensor networks, information and network security, web security, internet of things, bioinformatics and geoinformatics. The book is a collection of best papers submitted in the First International Conference on Computational Intelligence and Informatics (ICCII 2016) held during 28-30 May 2016 at JNTUH CEH, Hyderabad, India. It was hosted by Department of Computer Science and Engineering, JNTUH College of Engineering in association with Division V (Education & Research) CSI, India.
Includes author index.
Keywords: Computational intelligence -- Congresses.; Information theory -- Congresses.; elektronické knihy; electronic books